Supernumerary (B-) chromosomes in the Malayan house rat, Rattus rattus diardii (Rodentia, Muridae) - Yong, Hoi Sen; Dhaliwal, S.S. (Springer Verlag (Germany), 1972)
Three widely separated Malayan populations of Black rat, Rattus rattus diardii (Jentink), were found to comprise individuals with supernumerary (or B) chromosomes. The number of supernumeraries varied from 0 to 4. The incidence of B's in the three populations did not differ significantly. There was also no difference between the two sexes.